Penerapan Metode EOQ, EOI, dan ROP dalam Manajemen Pengadaan Obat: Studi Kasus di Apotek Berkah Dalem 2 Kabupaten Semarang - Fransisca Gloria; Anik Setyowati; Anisa Devi Kharisma Wibowo; Gilang Rizki Alfarizi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background. Pharmacies play an important role in health services by providing quality and safe drugs, but uneven drug stocks still cause shortages and excess drug supplies, this is the main challenge. Purpose. This study aims to analyze drug planning and procurement at Berkah Dalem 2 Pharmacy using the Economic Order Quantity (EOQ), Economic Quantity Interval (EOI), and Reorder Point (ROP) methods. Analysis results. The EOQ method shows that the economic order quantity for Cataflam 50 mg tablets is 48 tablets, while for Zoralin tablets it is 118 tablets. The EOQ method can save costs by 9% per month. The ordering interval based on the EOI method for Cataflam tablets is 22 days and for Zoralin tablets is 30 days, with ROP of 4 tablets and 6 tablets, respectively. Analysis using SPSS shows a significant relationship between the EOQ value and the usage value, indicating that the higher the EOQ value, the higher the usage value (p <0.05). These findings emphasize the importance of effective medication stock management to improve efficiency and patient satisfaction in pharmacies. This research has no conflicts of interest and was not funded.